Discrimination in Context: Examining Neighborhood-Level Variation in the Incidence and Adverse Effects of Perceived Racial and Ethnic Discrimination Among Chicago Youth - Zimmerman, Gregory M. (Race and social problems, 2023)
A growing body of research links interpersonal racial and ethnic discrimination to adverse youth outcomes. Yet, studies examining the relevance of neighborhood context for discrimination are sparse. This study examines neighborhood-level variation in the incidence and impact of perceived racial and ethnic discrimination on depressive symptoms, suicidal behavior, violent behavior, and substance use. Hierarchical regression models on a sample of 1333 African American and Hispanic youth (52.44% female; x̄ = 13.03 years, SD = 3.25 at wave 1) residing in 238 Chicago neighborhoods from the Project on Human Development in Chicago Neighborhoods indicated little to no neighborhood-level variation in the incidence and impact of discrimination. Findings suggest that the experience of discrimination among youth of color is ubiquitous.